Family eating and physical activity practices among African American, Filipino American, and Hispanic American families: Implications for developing obesity prevention programs - Luz Sobong Porter (JMIR Publications, 2017)
Overweight and obesity among children and adults is well-documented as an escalating problem. The purpose of this study is to determine the blood pressure, self-esteem, and eating and physical activity practices among African Americans, Filipino Americans, and Hispanic Americans; and project implications for development of childhood obesity prevention programs. This descriptive study was conducted in a convenience sample of 110 mothers recruited in health clinics and community centers located in Southeast Florida: 19% African Americans, 26% Filipino Americans, and 55% Hispanic Americans. The data, collected via self-administered questionnaires and a guided interview (Family Eating and Activity Habits Questionnaire, Rosenberg's Self-Esteem Scale, Background Information Questionnaire), were analyzed via descriptive and inferential statistics with findings significant at p < .05. Results revealed differences and similarities in eating and activity practices between Filipinos and Blacks or Hispanics. Blood pressure and self-esteem did not differ by ethnicity; however, overweight mothers tended to have overweight children. The results point clearly to the importance of the mothers' role modeling in eating and physical activity practices of families, reflecting the influence of mothers' behaviors in children's healthy behaviors, albeit family health. Given that mothers own physical exercise and eating habits could influence their children's physical activity levels and food choices, a parental advice strategy could be disseminated directly to parents by health professionals. Study findings may raise public awareness of the increasing prevalence and consequences of overweight and obesity in children and adolescents, particularly among vulnerable ethnic groups. The findings provide a database for nurse practitioners and other health service providers for the development of culturally sensitive focused public health education programs to prevent or control obesity.